DIGITALIZATION OF (ZIS) ZAKAT INFAQ AND SHADAQAH THROUGH THE USE OF QRIS (CASE STUDY: GENERATION Z) - Ahmad Zikry Fadillah; Putri Oktavia Rusadi; Asih Karsinih (Airlangga International Journal of Islamic Economics and Finance, 2022)
Zakat, infaq and shadaqah (ZIS) as social financial instruments in Islam has a role in improving the social economy of society. Research research results The BAZNAS strategy as of December 2021 notes that the total potential for zakat on in 2020 it has reached IDR 327.6 trillion. This potential is supported by the level of generosity of the Indonesian people is high because of the majority Muslim. Charities Aid Foundation (CAF) World Giving Index in 2021 places Indonesia in first place as the country with the most philanthropist in the world. Based on BAZNAS data in 2021, collection ZIS funds have seen an increase of 33% over 2020 in total collected Rp. 513.3 billion or an increase from the initial target. But amount the accumulated ZISWAF funds are not comparable to their potential reached IDR 327.6 trillion. In today's digital era, financial transactions on the ZIS instrument is an alternative solution so that the collection of ZIS funds can be more maximum. Survey conducted by the Association of Internet Service Providers Indonesia (APJII) in 2021, noted that internet users in Indonesia an increase of 11% from the previous year, namely from 175.4 million to 202.6 million user. This has implications for the development of e-lifestyle (lifestyle digital) in the era of society 5.0. This research aims to offer a solution utilization of the use of QRIS in raising ZIS funds in Indonesia. The Deputy Governor of Bank Indonesia stated that throughout 2021 transactions carried out using QRIS reached IDR 27.7 trillion or grew 237% (yoy). This study uses the critical literature review method, with review and analyze literature relevant to the research topic. Data used are primary data from surveys on generation Z and secondary data. The results of the study show that the collection of ZIS funds is through the use of QRIS has an impact on increasing ZIS fundraising. So funds ZIS can have a more significant impact in supporting poverty alleviation listed in the Sustainable Development Goals (SDGs).